The innovator's method : bringing the lean start-up into your organization - Furr, Nathan R.; Dyer, Jeff (Professor of strategy); Christensen, Clayton M. (Boston, Massachusetts : Harvard Business Review Press, 2014)
"Call it 'lean start-up, ' 'design thinking, ' or 'agile.' No matter the name, it's clear that a new method is revolutionizing how to successfully create, refine, and bring ideas to market without traditional business planning. But because these ideas and techniques run counter to conventional managerial thinking and practice, managers in established organizations have difficulty implementing them. No longer. Based on field work with thousands of managers and validated inside dozens of companies, innovation experts Nathan Furr and Jeff Dyer show when and how to apply a 'lean start-up' approach to innovation in established businesses"--
The innovator's method -- Leadership in the age of uncertainty -- Insight : savor surprises -- Problem : discover the job-to-be-done -- Solution : prototype the minimum "awesome" product -- Business model : validate the go-to-market strategy -- Master the pivot -- Scale it -- Making the innovator's method work for you -- Turn uncertainty into opportunity -- Appendix. An overview of the innovator's method.
Includes bibliographical references (pages 243-250) and index.
English.
Online resource; title from digital title page (viewed on October 30, 2019).
OCLC control number change
Keywords: Organizational effectiveness; Management -- Technological innovations; Consumers' preferences; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Strategic Planning; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Innovations; Création d'entreprises.; Esprit d'entreprise.; Marketing; Efficacité; Compétitivité; Consumers' preferences; Management -- Technological innovations; Organizational effectiveness; Innovation; elektronické knihy; electronic books